Software Nursing Sizing for nurses sizing in hospital obstetric care (Research, Society and Development, 2022)
Introduction: The creation of technological devices to support a safe practice in nursing is crucial for the improvement of care, especially in hospital obstetric, given the specificity and sensitivity of the care required in these environments. Objective: to demonstrate the process of developing a prototype of a software to calculate the number of nurses in the provision of hospital obstetric care. Method: Technological development study divided into three stages: exploration of the literature to identify the indicators to compose the instrument; validation by twelve specialist nurses in the area of investigation and statistical analysis by applying the Content Validity Index and Cronbach's Alpha Coefficient; development of the software prototype. Results: 17 indicators were included in the preliminary version of the instrument. After evaluation by the specialists, twelve indicators were included, with satisfactory evaluation by the Content Validity Index and Cronbach's Alpha coefficient of 0.7. The Software have good communication of its functions through access to the relational database, connections with textual elements, interface, warnings and control sequences. Conclusion: The software prototype fills a gap in the area of obstetric nursing and constitutes a technology for the management of nursing care in obstetrics, with the presentation of valid metrics giving quality to the technology and with useful features in hospital obstetric clinical practice of personnel sizing In this it is possible for the user to record data, transform them into information with graphics, and observe over time whether or not there have been changes in the institution.